BL_GERICHTE 720 12 362 / 207 vom 9. Mai 2011 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht vom 29. August 2013 (720 12 362 / 207) - BL Gerichte (2011)
Berufliche Massnahmen